2000
DOI: 10.1063/1.480579
|View full text |Cite
|
Sign up to set email alerts
|

Test of a simple and flexible molecule model for α-, β-, and γ-S8 crystals

Abstract: Libertador 8250, (1429) Buenos Aires, Argentina. e-mails: clopasto@cnea.gov.ar and gamba@cnea.gov.ar S 8 is the most stable compound of elemental sulfur in solid and liquid phases, at ambient pressure and below 400K. Three crystalline phases of S 8 have been clearly identified in this range of thermodynamic parameters, although no calculation of its phase diagram has been performed yet. α-and γ-S 8 are orientationally ordered crystals while β-S 8 is measured as orientationally disordered. In this paper we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 19 publications
(36 reference statements)
1
25
0
Order By: Relevance
“…Our calculations showed that the simple and flexible molecule model succesfully reproduced most experimental data available on the three crystals [10,11], including structural and dynamical data of α-and γ-S 8 at STP, the high temperature orientationally disordered phase of β-S 8 at 375K and its low temperature ordered phase. Nevertheless, below 200 K this simple isotropic LJ model did not reproduce the 100 K structure of α-S 8 , as determined by a neutron and X-ray measurements [13].…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Our calculations showed that the simple and flexible molecule model succesfully reproduced most experimental data available on the three crystals [10,11], including structural and dynamical data of α-and γ-S 8 at STP, the high temperature orientationally disordered phase of β-S 8 at 375K and its low temperature ordered phase. Nevertheless, below 200 K this simple isotropic LJ model did not reproduce the 100 K structure of α-S 8 , as determined by a neutron and X-ray measurements [13].…”
Section: Introductionmentioning
confidence: 59%
“…Using the anisotropic LJ model ANI-S 4 , with distances d ani =0.1 and 0.6Å, the orthorhombic α-S 8 sample does not spontaneously show the structural phase transition to the monoclinic α'-S 8 , as was calculated with the isotropic LJ model when the temperature of the orthorhombic sample was decreased below 200 K [10,11]. Nevertheless, if a new series of simulations are performed on a sample that initially has the structure of the monoclinic α'-S 8 , this phase is calculated stable, in the time scale of our simulations (about 200 ps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 The DF data set and the accumulated experience of fitting molecular potential functional forms would allow an improved description of sulfur structure and dynamical properties. However, we need to perform millions of Monte Carlo ͑MC͒ moves per atom on systems with more than ϳ1000 atoms, so that our model describes satisfactorily TABLE I. Parameters of the potential energy model.…”
Section: B Test Of the Interatomic Potentialmentioning
confidence: 99%